2009
DOI: 10.2176/nmc.49.507
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Regional Blood Flow Induced by Unilateral Subthalamic Nucleus Stimulation in Patients With Parkinson's Disease

Abstract: Changes in regional cerebral blood flow (rCBF) induced by unilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN) were investigated in 7 consecutive patients with Parkinson's disease, 4 men and 3 women (mean age 62.3 ± 8.1 years), who underwent rCBF measurement by N-isopropyl-p-(iodine-123)-iodoamphetamine single photon emission computed tomography at rest before and after unilateral STN DBS preoperatively in the on-drug condition, and postoperatively in the on-drug and onstimulation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…This approach is supported by previous evidence of bilateral rCBF effects of unilateral stimulation [Tanei et al 2009; Arai et al 2008], and we compared the ipsilateral and contralateral rCBF changes to confirm that bilateral averaging did not mask effects of unilateral stimulation.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…This approach is supported by previous evidence of bilateral rCBF effects of unilateral stimulation [Tanei et al 2009; Arai et al 2008], and we compared the ipsilateral and contralateral rCBF changes to confirm that bilateral averaging did not mask effects of unilateral stimulation.…”
Section: Methodssupporting
confidence: 81%
“…Indeed the effects on gait in this study were more modest than those reported in response to clinically optimized DBS [Bastian et al 2003]. The influence of unilateral STN DBS on rCBF is not as well established, but accumulating evidence indicates that unilateral DBS produces bilateral rCBF responses [Tanei et al 2009; Arai et al 2008]. Bilateral connections of basal ganglia nuclei shown by anatomic studies [Marani et al 2008; Parent and Hazrati1995] likely account for the observed contralateral effects.…”
Section: Discussionmentioning
confidence: 70%
“…DC was increased in the left SFG of EOPD patients compared to YCs. The frontal gyrus is not only engaged in the control of motion (Tanei et al, 2009) but is also related to attention to the movement (Jueptner et al, 1997). It was proposed that overactivation of the SFG is a compensatory mechanism in EOPD (Long et al, 2012), which may also be characterized by altered regional volume and cerebral blood flow in this area (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the different patterns of spontaneous brain activity might reflect a difference in regional vulnerability across the PD subgroups. The frontal gyrus is involved in both control of motor processing (Tanei et al, 2009 ) and attention to action (Jueptner et al, 1997 ; Rowe et al, 2002 ). The associative circuit in the striatal-thalamo-cortical loop projects from associative cortical areas, such as the prefrontal cortex, to the caudate nucleus, and the putamen (Baglio et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%